Selected papers from the 5th Northumbria International Conference on Performance Measurement in Libraries and Information Services. (Vine (En ligne), 2004)
Describes the activities, processes and outcomes involved in the development of a searchable Webbased directory of toolkits to support the evaluation of information communication technologies in the higher education/further education sector. Explains the definitions and terminology used to define the notion of toolkits, evaluation and the tools listed within the directory. Briefly considers those tools and toolkits included in the database relating to performance measures and quality assessment. Concludes that the main outcome of this project has been the realisation that the notion and form o.